The Effect of Maltodextrin Concentration Variations on the Microencapsulation of Probiotics from Manonjaya Salak Fruit Juice (Salacca zalacca (Gaert.) Voss) - Nofriyaldi, Ali; Fakhirah, Deani Sucia; Nurzaman, Mochamad Herdi (Journal of Food and Pharmaceutical Sciences, 2025)
Probiotic beverages have weaknesses in terms of shelf life related to stability. One way to maintain the stability of probiotic beverages is to encapsulate them into microcapsules using maltodextrin. The objective of this study is to determine the characteristics and effects of varying maltodextrin concentrations F1 (20%), F2 (40%), F3 (60%) on the physical properties of microcapsules from Manonjaya salak fruit (Salacca zalacca) probiotic beverages. This study was conducted experimentally in the production of microcapsules using the freeze-drying method. Data were analyzed descriptively, including organoleptic evaluation, measurement of total lactic acid, pH, lactic acid bacteria (LAB) count, moisture content, and morphological characterization using a Scanning Electron Microscope (SEM). The results of the characteristics of Manonjaya snake fruit juice microencapsulation can be concluded that variations in maltodextrin concentration affect the characteristics of microcapsules where all formulas meet the requirements, except for the results of the water content test between 10–10.33% which does not meet the requirements (≤ 3%). Thus, further research is needed in optimizing the microencapsulation formula of snake fruit juice, such as using a combination of coatings, longer freeze drying optimization time, and evaporation of snake fruit juice.